Making Vancouver class, status and social boundaries, 1863 - 1913 - McDonald, Robert A. J. 1944- (UBC Press, 1996)
By distinguishing between two types of identity - class and social status - McDonald shows how middle and upper working-class residents formed a broad group of 'respectable' citizens that straddled class lines. By contrast, those at the top of the social structure constituted a self-conscious upper class, and those at the bottom, the 'immigrants,' the transient workers, and the poor, were regarded as 'outsiders.' Collective biographies of four groups of residents - business leaders, social leaders, civic politicians, and labour activists - illustrate the nature of the social relationships
Literaturverz. S. 288 - 305
Keywords: Sozialgeschichte 1883-1913; Classes sociales - Colombie-Britannique - Vancouver - Histoire; Sociale geschiedenis; Geschichte; Social classes -- British Columbia -- Vancouver -- History; Vancouver (C.-B.) - Conditions sociales; Vancouver (C.-B.) - Histoire; Vancouver (B.C.) -- History; Vancouver (B.C.) -- Social conditions; Vancouver -- British Columbia